Plant Spacing: A Key Husbandry Practice for Rainy Season Cabbage Production - Khatiwada, Purushottam P (Nepal Agriculture Research Journal, 2011)
A field experiment was accomplished to establish appropriate plant spacing for summer season cabbage production in the rain fed condition of the high hills of eastern Nepal. The experiment was conducted during the summer of 1997, 1998 and 1999. Five different plant spacings (45- 60-cm, 45- 50-cm, 45- 40-cm, 45- 30-cm and 45- 20-cm) and two varieties, Green Stone and Green Coronet were tested. The interactive effect between variety and spacing was nonsignificant. However, among the tested spacings, head yields were statistically higher at 45- 30- cm and 45- 20-cm plant spacings. There was a positive linear correlation between closer plant spacing and cabbage head yield. The number of unmarketable heads and the lowest head compactness was recorded in 45- 20-cm spacing. Spacing of 45- 30-cm was found more economical. Plant population can be maintained as high as 74,074 number ha-1 by decreasing the spacing from 75- 60-cm to 45- 30-cm for the rainy season cabbage cultivation in high hills. By using this spacing, as high as 35 t ha-1 Key words: Cabbage; Hybrid; Plant spacing; Rainy season DOI: http://dx.doi.org/10.3126/narj.v4i0.4869 Nepal Agriculture Research Journal Vol. 4&5, 2001/2002 Page: 48-55 Uploaded date: 9 June, 2011